Perbandingan efektivitas kompres hangat dan kompres dingin terhadap penurunan dismenorea pada remaja putri - Oktasari, Gayatri -; -, Misrawati -; Utami, Gamya Tri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to compare the effectiveness of a warm compress and cold compress to decrease dysmenorrhea in adolescent girls. The design of this research was